2021
DOI: 10.31223/x5jc86
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Past fires and post-fire impacts reconstructed from a southwest Australian stalagmite

Abstract: Our current understanding of climate and its relationship to fires is generally confined to the recent past where instrumental records and satellite imagery are available. Speleothem records of past environmental change provide a unique opportunity to explore fire frequency and intensity in the past, and the antecedent climatic conditions leading to fire events. Here, we compare fire sensitive geochemical signals in a stalagmite from Yonderup Cave, a shallow cave in Western Australia, where well-documented wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, precipitation source, precipitation amount, and precipitation type (i.e., snow or rainfall), as well as relative humidity, and temperature all can influence drip-water and stalagmite δ 18 O values (Banner et al, 2007;Fairchild and Baker, 2012;Oster et al, 2012;Luo et al, 2014;Baker et al, 2019). Furthermore, studies have shown that vegetation density and wildfire activity can impact hydrologic recharge to a cave system leading to dripwater δ 18 O variability (Nagra et al, 2016;Treble et al, 2016;McDonough et al, 2021). Trace element variability (Mg/Ca, Sr/ Ca, and Ba/Ca) and δ 13 C compositions are also influenced by precipitation amount as well as bedrock composition and pCO 2 ventilation regimes in a cave (Fairchild and Treble, 2009;Wong et al, 2011;Oster et al, 2012;Oster et al, 2014;Casteel and Banner, 2015;Oster et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, precipitation source, precipitation amount, and precipitation type (i.e., snow or rainfall), as well as relative humidity, and temperature all can influence drip-water and stalagmite δ 18 O values (Banner et al, 2007;Fairchild and Baker, 2012;Oster et al, 2012;Luo et al, 2014;Baker et al, 2019). Furthermore, studies have shown that vegetation density and wildfire activity can impact hydrologic recharge to a cave system leading to dripwater δ 18 O variability (Nagra et al, 2016;Treble et al, 2016;McDonough et al, 2021). Trace element variability (Mg/Ca, Sr/ Ca, and Ba/Ca) and δ 13 C compositions are also influenced by precipitation amount as well as bedrock composition and pCO 2 ventilation regimes in a cave (Fairchild and Treble, 2009;Wong et al, 2011;Oster et al, 2012;Oster et al, 2014;Casteel and Banner, 2015;Oster et al, 2015).…”
Section: Introductionmentioning
confidence: 99%